Open innovation to scale up the circular economy: Exploring the mediating role of Industry 4.0 technologies - Jesus, Gessica Mina Kim [UNESP] (2025)
By fostering the flow of ideas, knowledge and technologies, open innovation can contribute to the implementation of the circular economy. However, despite the synergy between open innovation and the circular economy, and especially the support that open innovation can provide in overcoming the innovation and technological barriers associated with the transition to circular business models, there are still few studies investigating the relationship between these themes. With the aim of filling this research gap, the present study analysed how open innovation affects the implementation of the circular economy and the mediating role of Industry 4.0 technologies, using absorptive capacity as a moderating factor. The study analysed data collected from 163 companies operating in Brazil. The main findings indicate that (i) the use of open innovation practices is favourable to circular economy implementation; (ii) Industry 4.0 technologies have a positive impact on the adoption of the circular economy and mediate the relationship between open innovation and the circular economy; (iii) absorptive capacity does not demonstrably moderate the relationship between open innovation and the circular economy. The results of the study show that open innovation practices, such as collaboration with external actors and the co-creation approach along with the adoption of Industry 4.0 technologies, are positive for the implementation of the circular economy.